Factors Affecting the Perceptions of Employees and Tribe Fit Members Medan Regarding Transactions at Bank Syariah Indonesia - Hotmaida Hotmaida; Ahmad Syakir; Nursantri Yanti (Majapahit Journal of Islamic Finance and Management, 2025)
The purpose of this study is to determine the effect of transaction services and usage on the perceptions of employees and Tribe Fit members at Bank Syariah Indonesia in Medan. The subjects of this study were employees and Tribe Fit members consisting of customer service staff, cleaning service staff, technical staff, and members totaling 100 people, of which 36 respondents were tested using the probability sampling method. The results of primary data processing using regression analysis show that there is a significant and positive relationship between the variables of service and usage on the perceptions of employees and members regarding Bank Syariah Indonesia transactions in Medan. Of the three independent variables, it appears that the service variable is the main variable that contributes the most to the perceptions of employees and members regarding Bank Syariah Indonesia transactions in Medan.